1991
DOI: 10.1159/000247702
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metastases from Follicular Thyroid Carcinoma: Histology, Immunohistology, and Electron Microscopy

Abstract: Cutaneous metastases from thyroid carcinoma are extremely rare. We report 2 cases of skin metastases from a follicular thyroid carcinoma. A 53-year-old female patient underwent subtotal thyroidectomy because of the clinical suspicion of malignancy. Histological examination of the resected tissue did not clearly prove malignant features. Eight years later a cutaneous metastasis erupted next to the operation site at the neck. A 66-year-old female patient noticed a growing solitary skin nodule in the occipitopari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…[15] Face, neck, chest, arm and pelvis are the other cutaneous sites of metastasis affected with scalp. [16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions.…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…[15] Face, neck, chest, arm and pelvis are the other cutaneous sites of metastasis affected with scalp. [16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions.…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…[13][14][15][16][17][18] Overall, females outnumber males (12:6); the mean age at presentation is about 65 (41-85), with locations of the skin metastases being the scalp (13 pts), neck (3 pts), face (2 pts) and others (2 pts). [13][14][15][16][17][18] Clinically, they mostly present as asymptomatic skin-colored or red, angioma-like, firm and mobile dermal and subcutaneous papules and nodules that range in size from a few millimeters to several centimeters in diameter and that can occasionally erode and ulcerate both superficially and deeply, into the bone. 19 A vascular appearance has indeed been identified in these lesions, to the point of even showing a pulsatile character upon Doppler echography.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastik karsinomlar için akciğer ve karaciğer beklenen metastaz yerleri olmakla birlikte, eşlik eden yaygın kemik ve cilt metastazı varlığı literatür-de sınırlı sayıda olguda bildirilmiştir (7,10).…”
Section: Discussionunclassified